Analisis Pengendalian Intern Atas Sistem Informasi Penjualan Terhadap Efektivitas Dan Efisiensi Penjualan PT. Enseval Putera Megatrading Tbk. - Ilham Firmansyah; Udi Pramiudi (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
As one form of organization, the company must have goals and objectives to be achieved. Sales accounting information system is one of the accounting information sub systems that explains how the procedures in carrying out sales activities. To realize the management of company activities effectively, efficiently, and internal controls are needed that can provide accurate and trustworthy information. To fulfill this, there are several elements which are the main characteristics of an internal control system, including; organizational structure that separates functional responsibilities appropriately, the existence of a system of authority and good bookkeeping procedures, sound practices must be carried out in carrying out the duties and functions of each section in the organization as well as the existence of an employee skill level in accordance with their responsibilities. The results of internal control research on the sales system owned by PT. Enseval Putera Megatrading Tbk. it is quite good and adequate, which includes elements of: control environment, risk assessment, healthy practices, employees whose quality is in accordance with their responsibilities, information and communication, and monitoring. The Role of Internal Control of the sales information system in increasing sales effectiveness and efficiency is very important. The internal sales control system implemented is effective, because it reached the 2018 sales target of Rp. 21.7 trillion, and the realization of the 2018 budget of Rp. 20.6 trillion (± 94.93%) and sales volume increased. Can be seen from the increase in sales volume in 2017 amounting to Rp. 19,669,096,571,146 while in 2018 the amount of Rp. 20,604,487,293,751. Keywords: Internal Control, Sales Information System, Sales Effectiveness and Efficiency